Protection Coordination of Distribution Network with Optimally Placed Distribution Generation (ELEKTRIKA- Journal of Electrical Engineering, 2019)
In this study, optimal distribution network protection coordination scheme with directional over current relays is developed. In addition, impact of optimally placed Distribution Generation (DG) on the protection coordination scheme is subsequently evaluated using relay Coordination Time Interval (CTI). As such, the study is carried out in two stages. In the first stage, optimal relays settings (time dial settings and pickup current) are determined. While in the second stage, the maximum DG penetration level with changes in the protection coordination is evaluated. Particle Swarm Optimization (PSO) algorithm, due to its faster convergence speed, is applied in both stages. The technique is implemented on the distribution section of the IEEE 14-bus and IEEE 30-bus systems and simulated in MATLAB. The simulation results obtained are compared with that obtained using hybrid Genetic Algorithm (GS) – Nonlinear Programming (NP) approach using relays pickup current and operating times as performance metrics. For the IEEE 14 bus system, the developed PSO-based relay coordination has reduced the relays pickup current and operating times by roughly 28% and 32% respectively compared with the hybrid GA-NLP technique. The optimal locations of the DGs are found to be bus 5, 8 and 12 which result in CTI of 0.233sec. While in the IEEE 30 bus system, the developed relay coordination has reduced the relays pickup current and operating times by roughly 31% and 34% respectively compared with the hybrid GA-NLP technique. Similarly, the optimal locations and sizes of the DGs are found to be bus 19, 26 and 30, which result in CTI of 0.462sec.
Keywords: —directional over current relays; distribution generation; coordination time interval; time dial settings; pickup current